An Assessment to Determine the Typology of Spaces for a Flood Evacuation Centre in Malaysia - Fadzi, Mohammad Noriman Mohd; Hasnan, Mohd Tajul Izrin Tajul; Hanapi, Nurul Liyana; Ghorbani, Sharona (MAJ - Malaysia Architectural Journal, 2023)
Flooding is a yearly tragedy in Malaysia, hence the need for evacuation centres is paramount. However, the majority of Malaysia's evacuation centres in flood-prone areas have been criticized for having problems, particularly with space management. As a result, the study aims to develop a recommended typology of spaces model for a flood evacuation centre in Malaysia based on local agreement and perception. Likert scale questionnaires are used as a quantitative strategy in this paper to fulfil the research purpose. Overall, the study suggests nine typologies of space that must be provided for flood evacuation centres in Malaysia.